Temperature and Fluid Pressurization Effects on Frictional Stability of Shale Faults Reactivated by Hydraulic Fracturing in the Changning Block, Southwest China. Issue 8 (20th August 2020) - An, Mengke; Zhang, Fengshou; Chen, Zhaowei; Elsworth, Derek; Zhang, Lianyang
Abstract: A shale fault reactivated during multistage hydraulic fracturing in the Changning block in the Sichuan Basin, southwest China, accompanied a cluster of small earthquakes with the largest reaching ML 0.8. We illuminate the underlying mechanisms of fault reactivation through measurements of frictional properties on simulated fault gouge under hydrothermal conditions. Velocity‐stepping experiments were performed at a confining pressure of 60 MPa, temperatures from 30 to 300°C, pore fluid pressures from 10 to 55 MPa, and shear velocities between 0.122 and 1.22 μm/s. Results show that the gouge is frictionally strong with coefficient of friction of 0.6–0.7 across all experimental conditions. At observed in situ pore fluid pressure (30 MPa), the slip stability response is characterized by velocity strengthening at temperatures of 30–200°C and velocity weakening at temperatures of 250–300°C. Increasing the pore fluid pressure can increase values of ( a − b ) at temperatures ≥200°C, narrowing the temperature range where velocity weakening occurs. At the in situ temperature (90°C), the simulated gouge shows only velocity strengthening behavior and aseismic slip at elevated pore fluid pressures, contrary to the observed seismicity. We postulate that the aseismic slip at elevated pore fluid pressures may trigger seismicity by activating adjacent earthquake‐prone faults. Plain Language Summary: The Sichuan Basin of southwest China is the host to an increasing number of induced earthquakes potentially linked to the hydraulic fracturing for shale gas extraction. To understand whether the deep shale faults would slip unstably during hydraulic fracturing, we measure the frictional properties of powdered deep shale fault rocks (as simulated fault gouge) from a well in the Changning block in the Sichuan Basin which was identified with fault reactivation during hydraulic fracturing. We found that the simulated gouge slips stably at lower temperatures but unstably at higher temperatures. Elevating the pore fluid pressure stabilizes the fault slip at in situ and higher temperatures, contrary to the field observations. We postulate that the shale fault is prone to stable slip at higher pore fluid pressure, but this slip further can lead to the slip of adjacent unstable faults. Our results highlight the importance of combined temperature and pore fluid pressure effects on assessing the potential of induced seismicity from fluid injection activities. Key Points: Frictional properties of a shale fault reactivated by hydraulic fracturing are measured using simulated gouge under hydrothermal conditions Gouge favors aseismic creep at in situ temperature and remains stable at elevated pore fluid pressure, contrary to observed seismicity Importance of combined temperature and pore fluid pressure effects on assessing the potential of injection induced seismicity is highlighted